Theoretical Study of the Spectral and Charge-Transport Parameters of an Electron-Transporting Material Bis(10-hydroxybenzo[h]qinolinato)beryllium (Bebq2) - Freidzon, Alexandra Ya; Safonov, Andrei A; Bagaturyants, Alexander A (Journal of physical chemistry. C, 2015)
The multireference XMCQDPT2/CASSCF method is used to get insight into the charge transport mechanism of bis(10-hydroxybenzo[h]quinolinato)beryllium (Bebq2) and to explain some features of its light absorption and emission in monomeric and dimeric forms. Energy profiles corresponding to electron and hole hopping in Bebq2 monomer and in three close-packed dimers that can occur in the solid phase are calculated. Our calculation revealed that charges and excitons could be either localized on individual ligands or delocalized over a pair of stacking ligands in dimers. Delocalized hole states serve as deep charge traps hindering hole transport. On the other hand, the electron states are localized, and hopping electron transport can take place with low barriers. The excited states of dimers exhibit exciton splitting. In some dimers, the transition dipole moment arrangement is unfavorable for luminescence. Therefore, our calculations explain why Bebq2 is an electron transporter (hole blocker) and why regular packing with ligand stacking in Bebq2 layers favors electron transport along the stacks but decreases luminescence.